'Because I am me': school bullying and the presentation of self in everyday school life. (7th February 2022) - Forsberg, Camilla; Horton, Paul
ABSTRACT: In this study, we draw on Erving Goffman's work on the presentation of self to explore responses by 12–15-year-old (i.e. 6th–9th grade) school students to an open-ended survey question about why they think they were bullied. In doing so, we contribute to a relatively unexplored aspect of school bullying research by focussing on how those students who are subjected to bullying understand their own bullying experiences. We focus in particular on explanations that focus on themselves as individuals. Utilising thematic analysis, we identified six themes: (1) Body, (2) Manner, (3) Social structures, (4) Opinions and interests, (5) Ability, and (6) Relations. Our analysis of the students' responses suggests that they were bullied because they were perceived as different in some sense, and that such understandings of difference are connected to broader social and societal norms. These findings have important implications for understandings of bullying as aggressive acts and suggest that rather than simply focussing on the negative behaviour of individuals, anti-bullying initiatives also need to focus on the social structures that underpin the understandings of difference that facilitate such behaviour.